2017
DOI: 10.1016/j.ijheatmasstransfer.2017.03.117
|View full text |Cite
|
Sign up to set email alerts
|

Heat transfer deterioration of aviation kerosene flowing in mini tubes at supercritical pressures

Abstract: Heat transfer performances of aviation kerosene flowing in mini tubes at supercritical pressures were investigated experimentally and numerically. A ten-species surrogate model with the extended correponding state was used to calculate the thermophysical and transport properties of kerosene and the Re-Normalization Group (RNG) k-ε turbulent model with the enhanced wall treatment was adopted to consider the turbulent effect. The numerical results agree well with the experimental data. Two types of heat transfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(5 citation statements)
references
References 26 publications
2
3
0
Order By: Relevance
“…The axial flow acceleration ability is notably enhanced in the near-wall region, which decreases the velocity difference between the near-wall and the core region visibly. Consequently, the turbulence weakens and the heat transfer is deteriorated, which is similar to the results of Huang et al [23] and Jackson et al [26]. That also explains the higher heat transfer resistance in the near-wall region r/R = 0.96-1.00.…”
Section: Mechanism Of the First Htd Under Uniform Heat Fluxsupporting
confidence: 85%
See 2 more Smart Citations
“…The axial flow acceleration ability is notably enhanced in the near-wall region, which decreases the velocity difference between the near-wall and the core region visibly. Consequently, the turbulence weakens and the heat transfer is deteriorated, which is similar to the results of Huang et al [23] and Jackson et al [26]. That also explains the higher heat transfer resistance in the near-wall region r/R = 0.96-1.00.…”
Section: Mechanism Of the First Htd Under Uniform Heat Fluxsupporting
confidence: 85%
“…As the fuel temperature exceeds a threshold value, around 800 K for most The HTD of supercritical carbon dioxide draws numerous research interests in the effects of buoyancy lift [14][15][16], micro-scale channels [17][18][19], thermal properties [20], and the working conditions [21,22]. Regarding the supercritical hydrocarbon fuel, two types of HTD of the supercritical hydrocarbon fuel in mini-tubes are observed, where the wall and bulk fluid temperature exceeds the pseudo-critical temperature [23][24][25]. The HTD mechanism is investigated both experimentally and numerically.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Li et al [26] observed the heat transfer enhancement of aviation kerosene RP-3 when the wall temperature was close to the pseudo-critical value. While in similar experiments [27,28], heat transfer deterioration was observed by several researchers. Except for compound hydrocarbon fuel, the heat transfer of pure hydrocarbon fuels at supercritical pressures was also investigated.…”
Section: Introductionsupporting
confidence: 66%
“…Middle zone, where the tube wall temperature is higher than the supercritical temperature. As the near wall fluid has very low density and low viscosity, comparison of numerical data and experimental data [23][24][25][26] for the thermo-physical properties of aviation kerosene at P = 3 Mpa can be found in our previous publication [27]. Good agreement has been reached between the calculated results and experimental data.…”
Section: Experimental Apparatusmentioning
confidence: 53%